2016
DOI: 10.1007/s00261-016-0768-x
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic body radiation therapy of liver tumors: post-treatment appearances and evaluation of treatment response: a pictorial review

Abstract: Stereotactic body radiation therapy (SBRT) is a noninvasive treatment technique for selected patients with primary liver tumors and liver-confined oligometastatic disease. Recently, SBRT has emerged as an alternative treatment option in non-surgical candidates and in whom percutaneous treatment methods are not possible or contraindicated. The experience with SBRT continues to grow. There are currently no imaging guidelines for assessment of tumor response and follow-up schedule following SBRT. SBRT produces ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 43 publications
4
25
0
Order By: Relevance
“…In the veno-occlusive zone, there was injury to the venule endothelial cells resulting in activation of the clotting cascade, with fibrin deposition and sinusoidal congestion. A recent study by Haddad et al [40] confirmed this pattern of histopathologic findings. Our analysis fits this proposed histologic picture, as HCC treated with SBRT can be persistently hyperenhancing on arterial phase, which could be explained by the giant cell reaction induced by radiation therapy; a finding which would result in arterial phase hyperenhancement.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…In the veno-occlusive zone, there was injury to the venule endothelial cells resulting in activation of the clotting cascade, with fibrin deposition and sinusoidal congestion. A recent study by Haddad et al [40] confirmed this pattern of histopathologic findings. Our analysis fits this proposed histologic picture, as HCC treated with SBRT can be persistently hyperenhancing on arterial phase, which could be explained by the giant cell reaction induced by radiation therapy; a finding which would result in arterial phase hyperenhancement.…”
Section: Discussionsupporting
confidence: 54%
“…Furthermore, the progressive loss of arterial phase hyperenhancment over time may be secondary to progressive cell death, coagulation necrosis and fibrosis induced by the targeted radiation. [40]…”
Section: Discussionmentioning
confidence: 99%
“…However, there was no grade 3 or higher biliary stricture, and only six patients had grade 1 mild dilation of the bile duct without significant bilirubin elevation or the need for endoscopic intervention. In addition, the irradiated liver showed focal atrophy in almost all patients, a previously well-known image finding 32 . Additional atrophy was observed with repeated SBRT, but other findings, such as distortion of vascular structure or biliary stricture, were not observed in the overlapping high-dose area.…”
Section: Discussionmentioning
confidence: 55%
“…Thus, both tumor and normal tissue responses, including possible vascular and biliary duct damage, are expected to manifest quickly, both radiographically and clinically. Manifestation of the effects of radiation on tumors and normal tissues tends to evolve over a more protracted time course . In particular, the posttreatment radiographic appearance of treated liver and liver tumors, including enhancement patterns, change over time.…”
Section: Comparison With Other Local Ablative Therapiesmentioning
confidence: 99%
“…Manifestation of the effects of radiation on tumors and normal tissues tends to evolve over a more protracted time course. (41,42) In particular, the posttreatment radiographic appearance of treated liver and liver tumors, including enhancement patterns, change over time. Thus, local control of treated lesions needs to be assessed over serial time points.…”
Section: Comparison With Other Local Ablative Therapiesmentioning
confidence: 99%